Bhlhe40/Sirt1 Axis-Regulated Mitophagy Is Implicated in All-Trans Retinoic Acid-Induced Spina Bifida Aperta - Zhao, Lu; Liu, Dan; Ma, Wei; Gu, Hui; Wei, Xiaowei; Luo, Wenting; Yuan, Zhengwei (Frontiers in Cell and Developmental Biology, 2021)
Neural tube defects (NTDs) are the most severe congenital malformations that result from failure of neural tube closure during early embryonic development, and the underlying molecular mechanisms remain elusive. Mitophagy is the best-known way of mitochondrial quality control. However, the role and regulation of mitophagy in NTDs have not yet been elucidated. In this study, we used an all-trans retinoic acid (ATRA)-induced rat model to investigate mitophagy and its underlying mechanism in spina bifida aperta (SBA). The results of western blot, immunofluorescence and RT-qPCR analyses indicated that mitophagy was impaired and Sirt1 was downregulated in SBA. Administration of resveratrol-a strong specific Sirt1 activator-activated Sirt1, thus attenuating autophagy suppression and ameliorating SBA. RNA-sequencing and bioinformatics analysis results indicated that transcriptional regulation played an important role in NTDs. A luciferase reporter assay was performed to demonstrate that the transcription factor Bhlhe40 directly bound to and negatively regulated Sirt1 expression. Further, we discovered that the Bhlhe40/Sirt1 axis regulated mitophagy in neural stem cells. Collectively, our results for the first time demonstrate that Bhlhe40/Sirt1 axis regulated mitophagy is implicated in ATRA-induced SBA. Our findings provide new insights into pathogenesis of NTDs and a basis for potential therapeutic targets for NTDs.